Estimativa de produção de biogás e potencial energético dos resíduos sólidos em Pau dos Ferros-RN - Morais, Larissa Nathane Lima de (Universidade Federal Rural do Semi-Árido, 2018)
The population growth coupled with economic and industrial development demanded a greater production of urban solid waste, thus hindering the integrated management and managing of the same. Knowing that the inadequate disposal of these wastes brings with it damages to the environment, such as the pollution of the different environmental compartments, besides the atmospheric pollution, the purpose of this work was to estimate the biogas production of urban solid waste in the city of Pau dos Ferros-RN, as well as to evaluate its potential for energy use. In the methodology has estimates were made of population growth and its subsequent generation of waste, intending to calculate the emission of methane and biogas. For this, the LandGEM model was used for calculations of estimates of the gases generated by the waste. The evaluation was carried out in three different scenarios: the allocation of all waste to landfill (1), the disposal of organic food waste for composting (2) and the disposal of all waste for pyrolysis (3). As results has observed that the scenario that presented the highest biogas production was scenario 1 due to the high organic load present in the waste composition. While scenario 2 presented lower gas production than scenario 1, the low biogas generation occurs due to the removal of the organic fraction from the waste that would be sent to composted, essential to produce this gas. The scenario 3 presented a lower biogas emission due to the fact that it received only the residue resulting from the pyrolysis process and that it does not have a large potential for biogas generation Therefore, when conducting such solid waste treatment in the city of Pau dos Ferros -RN, such gases are prevented to be released into the atmosphere, thus preventing air pollution, in addition to the like in the disposed of solid waste required by the National Solid Waste Policy (NSWP). Relationed to the energy potential of the waste, it is possible that they can be used for the generation of electricity inside the landfill itself. However, more detailed studies are needed to verify the economic feasibility of the same.
Keywords: Tratamento de resíduos; Compostagem; Pirólise; Treatment; Compost; Pyrolysis; ENGENHARIAS::ENGENHARIA SANITARIA